2016
DOI: 10.1177/2327857916051019
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics and Prevention of Injuries From Needles Sticks and Sharps in the OR

Abstract: Aim: Implement ergonomic process improvement within the OR, to decrease incidence of injuries from sharps and needle sticks among the OR teams. Method: A pre and post intervention design was adopted. The number of reported incidents related to needle sticks and sharps over a seven month period prior to the implementation of the ergonomic process improvement(January to July 2014) and over a seven month period following implementation(January to July 2015), were compared. A participatory approach was adopted, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The following risk reduction strategies were extracted from Davis(2001) "Advanced Precautions in the OR"; Revised Statement on Sharps Safety(ACS, 2016); AORN, Sharps Safety, 2019 and Ergonomics and the prevention of NSIs in the OR (Kalaga, Balters and Crowley, et al, 2017). Two OR Ergonomics Surveys were created.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following risk reduction strategies were extracted from Davis(2001) "Advanced Precautions in the OR"; Revised Statement on Sharps Safety(ACS, 2016); AORN, Sharps Safety, 2019 and Ergonomics and the prevention of NSIs in the OR (Kalaga, Balters and Crowley, et al, 2017). Two OR Ergonomics Surveys were created.…”
Section: Methodsmentioning
confidence: 99%
“…Surgical tasks take place within a relatively small, constrained space, involving multiple hands in close proximity with moving sharps and minimal engineering controls to provide protection from injury. Kalaga, Balters, Crowley, et al,(2017) reported a process improvement study at a teaching hospital which included physical, cognitive and psychosocial ergonomic interventions, for reducing NSIs in the OR. They incorporated the successful interventions reported in the literature, and expanded ergonomic interventions for preventing NSI, including techniques for preventing localized fatigue/pain; cognitive aspects of managing attentional resources and team work, within the three phases of the OR task.…”
Section: Introductionmentioning
confidence: 99%